2004
DOI: 10.1007/s00204-004-0578-8
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of inorganic mercury salts based on disturbed microtubule function

Abstract: In order to investigate the chromosomal genotoxicity of nitrobenzene and benzonitrile, we studied the induction of micronuclei (MN) by these test compounds in V79 cells, as well as effects on the formation and stability of microtubules and on motor protein functions. No cytotoxicity was seen in V79 cell cultures in terms of Neutral red uptake after 18 h treatment with up to 1 mM nitrobenzene or 1 mM benzonitrile. Subsequently, a concentration range up to 100 micro M was used in the experiments on induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(24 citation statements)
references
References 39 publications
2
21
0
1
Order By: Relevance
“…8) as Hg 2+ entered the cell under hypotonic stress. Previous reports have shown that Hg 2+ disrupt both microtubules [48] and actin filaments [23]. Blebbing has been attributed to weakened adhesion between the bilayer and the cytoskeleton or disorganization of the cytoskeleton [49].…”
Section: Discussionmentioning
confidence: 99%
“…8) as Hg 2+ entered the cell under hypotonic stress. Previous reports have shown that Hg 2+ disrupt both microtubules [48] and actin filaments [23]. Blebbing has been attributed to weakened adhesion between the bilayer and the cytoskeleton or disorganization of the cytoskeleton [49].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies produced the following results: Mercury interferes with polymerization of microtubules [122,123], increases secretion of both 1-40 and 1-42 forms of Aβ and promotes hyperphosphorylation of tau protein [9,[124][125][126][127], changes mitochondrial structure inducing a stress-response in astrocytes [128], and interferes with cell-maturation [129] or other aspects of cell functioning, such as DNA repair, glutathione level, or linkage and structure of microtubules [119,130,131]. Mercury disturbs the interaction between tubulin and GTP [132], and the chelator DMSA can reverse this process [133], while amalgam exposure is toxic for nerve cells in vitro [134].…”
Section: Experimental Animal and In Vitro Studiesmentioning
confidence: 99%
“…This assay is a non-specific genotoxicity test that detects fixed mutations and permanent DNA damage. This test detects chromosomal aberrations as micronuclei in dividing versus non-dividing cells, 37 which serve as a good biomarker of exposure to genotoxins. The presence of a micronucleus represents the disruption of small amounts of non-condensed chromatin, and their increased frequency is evidence of prior structural chromosome damage or changes in chromosome number.…”
Section: Resultsmentioning
confidence: 99%